2021
DOI: 10.1186/s12915-021-01150-w
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of pelvic canal shape and rotational birth in humans

Abstract: Background The human foetus typically needs to rotate when passing through the tight birth canal because of the complex shape of the pelvis. In most women, the upper part, or inlet, of the birth canal has a round or mediolaterally oval shape, which is considered ideal for parturition, but it is unknown why the lower part of the birth canal has a pronounced anteroposteriorly oval shape. Results Here, we show that the shape of the lower birth canal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 97 publications
0
6
0
2
Order By: Relevance
“…For example, the ribcages of Homo erectus and Neandertals were not only wider at the level of the central and lower thorax, but also antero-posteriorly deeper than most modern human populations [1][2][3][4] . Also the pelvis shows a systemic evolutionary trend towards reduction of its bi-iliac width, when comparing modern humans with H. erectus and members of the Neandertal lineage [5][6][7][8] . Evolutionary changes in the spine of the genus Homo show changes in overall height, it's position within the ribcage and possibly spine curvatures.…”
Section: Evolutionary Anatomical Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the ribcages of Homo erectus and Neandertals were not only wider at the level of the central and lower thorax, but also antero-posteriorly deeper than most modern human populations [1][2][3][4] . Also the pelvis shows a systemic evolutionary trend towards reduction of its bi-iliac width, when comparing modern humans with H. erectus and members of the Neandertal lineage [5][6][7][8] . Evolutionary changes in the spine of the genus Homo show changes in overall height, it's position within the ribcage and possibly spine curvatures.…”
Section: Evolutionary Anatomical Changesmentioning
confidence: 99%
“…Besides a positive effect of overall trunk muscularity 26 , 30 on running performance, it has been shown that several other specific trunk morphological aspects relate to running performance, including the width of the pelvis 8 , 31 , the trunk flexion angle 32 , lumbar lordosis 33 , 34 and associated hip flexion 31 , and thorax breathing mechanics 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, estos planos presentan diferentes orientaciones y diámetros que están delimitados por los rebordes óseos y las estructuras músculo-aponeuróticas. Esto obliga al feto a realizar no solamente un trayecto curvo en su descenso, sino además una rotación similar a un movimiento de tornillo de ¼ a ¾ de vuelta (8,9) . De forma esquemática, el canal del parto puede analizarse a partir de una entrada o espacio superior, un espacio medio y una salida o espacio inferior.…”
Section: La Pelvis: Su Forma Y Movimientos Intrínsecosunclassified
“…Los hombros deben seguir el movimiento de la cabeza realizando su primera rotación: desde la posición sagital o anteroposterior a la posición transversa u oblicua. Si el dorso es izquierdo, el hombro anterior o derecho se relaciona con la línea pectínea derecha y el hombro posterior o izquierdo se relaciona con la línea innominada izquierda (9) . Este último es el primero que debe penetrar en la pelvis, pues es el más distante de la salida y el más sometido a la tracción.…”
Section: El Recorrido De Los Hombrosunclassified
“…That is, the assumption at the heart of the OD—that pelvic width is constrained by locomotor energy expenditure—is unsupported by convincing empirical evidence in modern humans. Sufficient questions remain to be answered, however, before the metabolic energy clause of the OD can be completely rejected [ 11 ] and other potential causes (e.g., pelvic floor integrity [ 31 , 32 ], femoral neck fracture risk [ 33 ] emphasized.…”
Section: Introductionmentioning
confidence: 99%